Evaluation of Direct/Indirect Pulp Capping Procedures Requiring Root Canal Therapy - Nurul Syamimi binti Mohd Azlan Sunil1 , Revathi Duraisamy2 , Iffat Nasim (Indian Journal of Forensic Medicine & Toxicology, 2020)
The common objective of pulp capping is to induce a physical protective barrier over the pulp to maintain thevitality and function of the tooth. Indirect pulp capping is done in cases where deep carious lesions are foundin tooth and lesion is adjacent to vital pulp tissues. Pulp capping remains a controversial topic as opinions onpulp capping treatment vary from clinicians, despite new advances gained through research. Many cliniciansare reluctant to opt for direct pulp capping as a treatment option in cases of carious exposed pulp may be dueto conflicting data and findings reported regarding success rate of pulp capping. The aim of this study wasto evaluate the number of direct/indirect pulp capping cases which underwent root canal therapy. This studyincluded adults above 18 years who had previously undergone direct/indirect pulp capping and reportedto dental hospital between June 2019 to March 2020. Around 86000 patient records were reviewed andanalysed for the inclusion criteria and the following parameters were extracted; (i) Patient’s gender, (ii) typeof pulp capping, (iii) teeth involved and (iv) teeth which underwent root canal therapy. Data was recordedin Microsoft Office Excel (2013) and analysed using SPSS Software Version 26.0. Chi-square test was doneto find out correlation between variables. Significant level test was set at p<0.05. A total of 218 teeth werefound to have undergone pulp capping, those of which were 33.9% direct pulp capped tooth and 66.1%indirect pulp capped tooth. The teeth involved were 4.1% anteriors, 9.6% premolars and 86.2% molars.18.8% of capped teeth underwent root canal therapy. More females (21%) underwent root canal therapythan males (17.5%). A higher percentage of premolars underwent root canal therapy compared to other teeth(42.9%) and more indirect pulp capped teeth underwent root canal therapy (20.1%) than direct pulp cappedteeth (16.2%). Within the limits of this study, it was observed that the number of pulp capping cases whichunderwent root canal therapy is about one fifth and was more commonly seen in premolars and in indirectpulp capping cases.